2008
DOI: 10.1111/j.1471-0528.2008.01726.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate or delayed repair of obstetric anal sphincter tears—a randomised controlled trial*

Abstract: Objective To investigate if an 8-to 12-hour time delay of primary repair affects anal incontinence at 1-year follow up.Design Randomised controlled trial.Setting University hospital in Sweden.Population A total of 165 women diagnosed with a third-to fourth-degree perineal tear.Methods The participants were randomised to immediate or delayed (8-to 12-hour delay) end-to-end repair; 78 were allocated to immediate operation and 87 to a delayed repair. An incontinence and pelvic floor symptom questionnaire was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 47 publications
(53 reference statements)
1
20
0
2
Order By: Relevance
“…With respect to time of intervention, late (up to 12 hours) repair does not seem to produce an inferior functional result 1 year after surgery, 8 although immediate surgery's main advantages are emotional comfort of the woman in this important moment of her life, control of possible active bleeding, and avoidance of tissue edema and infection. 7…”
Section: Discussionmentioning
confidence: 92%
“…With respect to time of intervention, late (up to 12 hours) repair does not seem to produce an inferior functional result 1 year after surgery, 8 although immediate surgery's main advantages are emotional comfort of the woman in this important moment of her life, control of possible active bleeding, and avoidance of tissue edema and infection. 7…”
Section: Discussionmentioning
confidence: 92%
“…Sphincter repair can be deferred due to any inconvenient causes without deteriorating functional outcomes. One randomized control trial in 2008 comparing immediate repair and delayed repair (8–12‐h delay) reported that there were similar functional outcomes at the 1‐year follow‐up . Furthermore, Soerensen et al .…”
Section: Prevalence and Incidencementioning
confidence: 99%
“…This paper was based on 108 patients taken from an original cohort of 165 women who were randomized to immediate or delayed end-to-end repair after a third-degree to fourthdegree perineal tear [17]. Of these 108 women, 20 had anal incontinence, predominantly for flatus; only four were incontinent for loose or solid stool and nearly 90% of these patients had a third-degree perineal tear.…”
Section: What Factors Influence the Risk Of Fecal Incontinence After mentioning
confidence: 99%
“…Analyses focused on conditions that preceded the incidence date of FI for cases in each matched pair. In 88% of cases, FI began at age ≥40; severity was mild (37%), moderate (58%), or severe (5% [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and stress urinary incontinence (OR, 3.1; 95% CI, 1.4-6.5), but not obstetric events, were independent risk factors for FI. These data demonstrate that bowel disturbances rather than prior obstetric injury are the main risk factors preceding the onset of FI.…”
Section: What Are the Risk Factors For Fecal Incontinence In The Commmentioning
confidence: 99%